Limitation of diagnostic value of cone-beam CT in detecting apical root isthmuses - Elen de Souza TOLENTINO; Pablo Andrés AMOROSO-SILVA; Murilo Priori ALCALDE; Heitor Marques HONÓRIO; Lilian Cristina Vessoni IWAKI; Izabel Regina Fischer RUBIRA-BULLEN; Marco Antônio HÚNGARO-DUARTE (University of São Paulo, 2020)
Abstract Isthmuses are reported as common anatomic complexities in teeth often associated with failures in endodontic treatment. They should be considered before starting treatment and a preoperative computed tomography scan (CT) may demonstrate these complexities. Objective To assess the diagnostic value of the highest resolution settings of a cone-beam CT (CBCT) system in identifying and measuring apical isthmuses, using micro-CT as reference. Methodology After micro-CT scanning, 40 humans' lower first molars with isthmuses in the apical-3 mm of mesial roots were scanned by the highest resolution settings of the New Generation i-Cat ® CBCT equipment. Two blinded observers recorded the detection of isthmuses in CBCT scans. The lengths of isthmuses were compared between micro-CT and CBCT to assess the diagnostic value of CBCT. Quantitative data for sensitivity were represented as percentages (95% confidence interval). The Bland-Altman method was used to assess differences between gold standard lengths (micro-CT) and CBCT lengths. Results BCT demonstrated 30 positive findings, representing sensitivity for isthmus identification of 75% (95% CI=0.4114-1.1364). Differences between the lengths in micro-CT (1.99±0.40 mm) and CBCT (1.53±0.41 mm) were significant (p<0.0001). Conclusion The CBCT device used presented limited diagnostic value in the identification and measurement of apical isthmuses in the mesial roots of lower molars. In some cases, the actual anatomy of the apical root canal may not be completely delineated in this type of CBCT system, even using the highest resolution settings.